A Single-Step Purification and Molecular Characterization of Functional Shiga Toxin 2 Variants from Pathogenic Escherichia coli - Robert E. Mandrell; Stephanie McMahon; Beatriz Quiñones; Xiaohua He (Toxins, 2012)
A one-step affinity chromatography method was developed to purify Shiga toxin 2 variants (Stx2) Stx2a, Stx2c, Stx2d and Stx2g from bacterial culture supernatants. Analysis of the purified Stx2 variants by denaturing gel electrophoresis revealed 32 kDa and 7 kDa protein bands, corresponding to the Stx2A- and B-subunits, respectively. However, native gel electrophoresis indicated that purified Stx2c and Stx2d were significantly higher in molecular weight than Stx2a and Stx2g. In a cytotoxicity assay with Hela cells, the 50% cytotoxic dose of Stx2a and Stx2g were 100 pg and 10 pg, respectively, but 1 ng each for Stx2c and Stx2d. Interestingly, analysis of the 50% inhibitory dose in a cell-free translational system from rabbit reticulocyte lysates indicated that Stx2g had a lower capacity to inhibit protein synthesis than the other Stx2 variants. The cytotoxicities in Hela cells were neutralized with an anti-Stx2B antibody and were denatured at 80 °C for 1 h. These findings demonstrated that Stx2 variants exhibited different toxicities, holotoxin structure, and stabilities using distinct systems for assessing toxin activities. The development of a simple method for purification of Stx2 variants will enable further studies of Stx2-mediated toxicity in various model systems.